Utility of the multi-component training distress scale to monitor swimmers during periods of training overload - Main, L. C.; Warmington, S. A.; Korn, E.; Gastin, P. G. (Research in Sports Medicine, 2016)
The purpose of the present study was to determine the efficacy of the multi-component training distress scale (MTDS), in monitoring swimmers prior to national competition. Twenty-one national-level adolescent swimmers completed eight weeks of testing. Once a week participants completed an 8 × 50 m sprint test, vertical jump test, sit-and-reach test, the MTDS and the Recovery-Stress Questionnaire for Athletes (REST-Q). All testing was incorporated into the swimmers` normal training programme. The REST-Q accounted for the following variances in performance: flexibility (14.6%, p = 0.009), power output (17.7%, p = 0.003), swimming speed (15.5%, p = 0.006) and swimming endurance (17.5%, p = 0.002). In comparison, the MTDS accounted for the following variances in performance: flexibility (12.1%, p = 0.095), power output (16.4%, p = 0.023), swimming speed (20.5%, p = 0.003) and swimming speed endurance (23.8%, p = 0.001). The findings of the current study suggest that both the REST-Q Sport and the MTDS have the capacity to predict performance on a range of fitness components associated with swimming.